MARS/NDRI/KSU Communications Workshop: Part 4. Nominal Group Discussions - Leslie, John F. (My University, 2022)
A. Nominal Group Discussion Process Description – Pages 1-2 B. Sample Results from Dhulikhel Conference – Page 3 C. Nominal Group Question Organization Matrices for Days 1 and 2 – Page 4 D. Interpreting Nominal Group Discussion Results – Pages 5-6
Keywords: Aflatoxin; Food Safety; Mycotoxins; Nepal; Public Health; Risk Communication